Exploring barriers and facilitators for the potential implementation of the decision tool-functional independence in primary care - E. A. L. M. Molenaar; J. A. Barten; N. Bleijenberg; N. J. de Wit; C. Veenhof (BMC Health Services Research)
Abstract Background The aging population presents challenges for healthcare, particularly in maintaining the functional independence of older adults. The Decision Support Tool for Functional Independence was developed to identify declines in functional independence and promote collaboration between healthcare professionals. The DST-FI is specifically designed to support interprofessional collaboration between medical and social care providers, such as GPs, physiotherapists, nurses, and social workers. This study examines the barriers and facilitators to implementing the tool in primary care. Methods This study was conducted in the Netherlands and included thirteen healthcare professionals—general practitioners, physiotherapists, practice nurses, community nurses, occupational therapists, and social workers—as well as two focus groups with older adults. The study was guided by the Consolidated Framework for Implementation Research (CFIR). A combination of deductive and inductive thematic analysis was used to identify and explore barriers and facilitators to implementation. Results Key facilitators included the tool’s potential to enhance collaboration, support informed decision-making, and address societal pressures related to aging. However, four main barriers emerged: limited applicability for specific client groups (e.g., individuals with cognitive impairments or low health literacy), time constraints, issues of ownership among stakeholders, and challenges in preventive outreach. Conclusions The diversity and complexity of factors influencing the implementation of the Decision Support Tool for Functional Independence highlight the need for multifaceted, tailored strategies. Future research should focus on developing customized approaches to overcome identified barriers, exploring adaptations for a broader audience, and determining the appropriate healthcare professionals for the tool’s practical application. The potential of the tool to foster interprofessional collaboration between general practitioners, physiotherapists, nurses, and social workers. and alleviate societal challenges, emphasizing its relevance in primary care.